2023
DOI: 10.1021/acs.iecr.3c02395
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Mesoporous Aluminosilicates with Moderate Acidity and High Hydrothermal Stability by Acid-Free Method

Hongtao Liu,
Jiayu Zhou,
Gen Li
et al.

Abstract: Mesoporous aluminosilicates (MAs) are promising catalytic materials for large molecule cracking. However, this material still suffers from poor stability and weak acidity. Synthesis of MAs with enhanced acidity and excellent hydrothermal stability is very desirable. In this study, we propose the facile obtaining of hydrothermally stable Al-SBA-15 with moderate acidity by using a sodium persulfate strategy in an acid-free medium. The obtained Al-SBA-15 exhibits large surface areas (430 m 2 /g), superior hydroth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…Besides, it can also be found that the specific surface area of all used OCs decreased by about 50% and so did the pore volume except for the pure Fe 2 O 3 , indicating serious sintering occurred for the Fe 2 O 3 -based OCs, even so, the specific surface area and pore volume of the used Fe 2 O 3 -activated Al 2 O 3 and Fe 2 O 3 –AlOOH are still much larger than those of the fresh pure Fe 2 O 3 . Moreover, a mesoporous structure was obtained for those Fe 2 O 3 -based OCs according to the type IV N 2 ad-desorption curves and H3 hysteresis loops as displayed in the Figure , which is further validated by the pore size distribution profiles as shown in Figure S4. Furthermore, compared to the fresh OCs, nearly unchanged pore size was observed for the cycled pure Fe 2 O 3 and Fe 2 O 3 -inert Al 2 O 3 , while a mesopore-decreasing and macropore-increasing trend was exhibited for other OCs.…”
Section: Resultsmentioning
confidence: 99%
“…Besides, it can also be found that the specific surface area of all used OCs decreased by about 50% and so did the pore volume except for the pure Fe 2 O 3 , indicating serious sintering occurred for the Fe 2 O 3 -based OCs, even so, the specific surface area and pore volume of the used Fe 2 O 3 -activated Al 2 O 3 and Fe 2 O 3 –AlOOH are still much larger than those of the fresh pure Fe 2 O 3 . Moreover, a mesoporous structure was obtained for those Fe 2 O 3 -based OCs according to the type IV N 2 ad-desorption curves and H3 hysteresis loops as displayed in the Figure , which is further validated by the pore size distribution profiles as shown in Figure S4. Furthermore, compared to the fresh OCs, nearly unchanged pore size was observed for the cycled pure Fe 2 O 3 and Fe 2 O 3 -inert Al 2 O 3 , while a mesopore-decreasing and macropore-increasing trend was exhibited for other OCs.…”
Section: Resultsmentioning
confidence: 99%